Practical Aspects of Computational Chemistry III - Leszczynski, Jerzy; Shukla, Manoj K. (Springer US : Imprint: Springer, 2014)
Theoretical and Computational Chemistry research has made unparalleled advancements in understanding every expanding area of science and technology. This volume presents the state-of-the-art research and progress made by eminent researchers in the area of theoretical computational chemistry and physics. The title mirrors the name of the annual international conference "Conference on Current Trends on Computational Chemistry" (CCTCC) which has become a popular discussion ground for eminent Theoretical and Computational Chemists and has been honored by the presence of several Nobel Laureates. Practical Aspects of Computational Chemistry III is aimed at theoretical and computational chemists, physical chemists, material scientists, and those who are eager to apply computational chemistry methods to problems of chemical and physical importance. The book is a valuable resource for undergraduate, graduate, and PhD students as well as established researchers.